(3GdSjGSI ai Yde GdaQGSIs - (3TjN GdQHhI , CHh YHO Gddg eMeO Hf CHj WGdH GdCfUGQj GdUhaj GdOeTbj, TjN GdQHhg (B/ (3TjN MWjf,J (B727 (3g` s
(3ChdgG (B:s
(3GeG HYO agPg QSGdI eTJedI Ydi eYGbO LeYI ef Yde GdaQGSI dCLd GdSjGSI hGdcdGe s
(3BNQgG (B:s
(3JeJ GdbVGjG GdNeSI hYTQjf bVjI hGddg CYde hCMce HGdUhGH Je cJGH Yde GdaQGSI s
(3fSNI NGeSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B170 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B94s
(3eUOQ GbJfGA GdCUd (B:s
(3GdChbGa (B_ (3GdehUd (B/ (3GdYQGb (B(11/9) s
Keywords: (3GdaQGSIs